Quality Control Management Of Madrasah Education In International Standard - Indah Komsiyah (International Journal of Science, Technology & Management, 2022)
Quality control has to design in educational institutions. The purpose of this study was to determine the concept of quality control of education at the International Standard Madrasah Amanatul Ummah Pacet Mojokerto, East Java. This research is qualitative research with a single case study model. The participants involved are 1) kyai, 2) madrasa heads, 3) vice coordinators of Madrasas, 4) ustadzor teachers in Madrasas, 5) students, and 6) alumni. The data collection process is 1) in-depth interviews; 2) participant observation; and 3) documentation studies. Data analysis data used l) data reduction, 2) data display; and 3) conclusion drawing/verification. The finding shows that the quality control process at the International Standard Madrasah Amanatul Ummah includes, 1) monitoring of activity programs is carried out in a coordinated and responsible manner; 2) a series of evaluations carried out intensely; 3) carry out control of order and program implementation continuously; 4) activity report in written form in the form of reporting and verbally in the form of directions; 5) carry out continuous monitoring. While transcendent control is a form of inherent supervision that is embedded in the religious spirit of each person relying on the Substance of the Almighty Creator. The control of improving the quality of education carried out by the Amanatul Ummah International Standard Madrasah is internal and transcendent control.